Adapting new norms: A mixed-method study exploring mental well-being challenges in dental technology education - Galvin Sim Siang Lin; Wen Wu Tan; Kah Hoay Chua; Jong-Eun Kim; Jin Gan; Mohd Haikal Muhamad Halil (PLoS ONE, 2025)
Background The present study, grounded in the Stress-Adaptation-Growth theory, aims to explore the mental well-being among dental technology students during the post-pandemic period. Materials and methods A mixed-method approach was employed among undergraduate dental technology students in Malaysia. The Depression, Anxiety, and Stress Scale (DASS-21) was adapted and modified for dental technology students. The content of the questionnaire was validated by two experienced faculty experts. Construct validity and internal consistency were measured. An online survey was created using Google Forms and disseminated to 10 Bachelor of Dental Technology (BDT) students. Meanwhile, qualitative data were obtained through one-on-one semi-structured interviews, employing a phenomenology approach and thematic analysis to explore students’ experiences in the new educational landscape. Results All students answered the survey, predominantly females. Prevalence of depression (60% normal, 10% mild, 30% moderate), anxiety (30% normal, 30% mild, 10% moderate, 10% severe, 20% extremely severe), and stress (70% normal, 10% mild, 10% moderate, 10% severe) was reported. Qualitatively, three major themes emerged: “Problems with adaptations”, “Anxious about returning to campus”, and “Concern about the future”. The first theme included sub-themes: “Difficulties in transitioning to hybrid learning” and “Disruption in study-life balance”. The second theme had four sub-themes: “Fear of being infected”, “Fear of being stigmatized”, “Increased vigilance in personal safety measures”, and “Confusion about standard operating procedure”. The third theme included sub-themes: “Fear of another lockdown” and “Concerns about timely completion of academic requirements”. Conclusions This study highlights the complex mental health challenges dental technology students faced post-pandemic, underscoring the need for flexible academic policies, global collaborations, and targeted strategies to support their resilience and well-being.